2017
DOI: 10.17707/agricultforest.63.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Presowing seed treatment methods to overcome dormancy in seeds of Vachellia rehmanniana Schinz

Abstract: and Natural Resources from November to December 2016. Mature Vachellia rehmanniana seeds were collected from healthy erect trees at Butale Village, Botswana to investigate the effect of different pre-sowing treatment methods on seed germination. The experiment was laid out in a completely randomized design (CRD) with five treatments (control, mechanical scarification, boiling water, hot water and concentrated sulphuric acid (98.8%)). Boiling water had three different levels of time exposure (1, 3 and 5 min) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 9 publications
(22 reference statements)
3
10
2
Order By: Relevance
“…violacea seedstreated in concentrated H2SO4to reach maximum germination. This is in agreement with others who usedH2SO4 treatments to overcome dormancy in seeds of many tree species (Teketay, 1996;Agbogidi et al, 2007;Likoswe et al,2008;Amusa, 2011;Aref et al,2011;Li et al, 2013;Fredrick et al, 2017;Mojeremane et al, 2017Mojeremane et al, , 2018. For example, Amusa (2011) reported that concentrated H2SO4 disrupts and exposes the lumens of the macrosclereids cells by disrupting the hard seed coat, thereby, allowing uptake of water to induce the germination process.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…violacea seedstreated in concentrated H2SO4to reach maximum germination. This is in agreement with others who usedH2SO4 treatments to overcome dormancy in seeds of many tree species (Teketay, 1996;Agbogidi et al, 2007;Likoswe et al,2008;Amusa, 2011;Aref et al,2011;Li et al, 2013;Fredrick et al, 2017;Mojeremane et al, 2017Mojeremane et al, , 2018. For example, Amusa (2011) reported that concentrated H2SO4 disrupts and exposes the lumens of the macrosclereids cells by disrupting the hard seed coat, thereby, allowing uptake of water to induce the germination process.…”
Section: Discussionsupporting
confidence: 91%
“…Maximum germination recorded in these treatments could probably be attributed to the uptake of water and gaseous exchangedue to softening or cracking of the seed coat (Teketay, 2005;Azad et al, 2011) which triggered the germination process (Teketay, 2005;Rasebeka et al, 2014). Mechanical scarification has been reported to break physical dormancy rendered by hard seed coats by enhancing gases and water uptake especially in leguminous species (Missanjo et al, 2014;Mojeremane et al, 2017Mojeremane et al, , 2018.Earlier germination in nicked P. violacea seeds in the present study could be due to cracks made on the seed creating entry of water and exchange of gases, resulting in enzymatic hydrolysis and, thus, transforming the embryo into a seedling. This is in agreement with others who demonstrated that nicking part of the hard seed coat, which prevents imbibition and gaseous exchange (Teketay, 2005;Azad et al,2011) triggered the germination process (Teketay, 2005;Olatunji et al, 2013).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations